PRO AND VERB MOVEMENT IN ARABIC SYNTAX - AlAlamat, Hamed (European Scientific Journal, ESJ, 2014)
This paper aims at investigating the properties of pro or the null subject in Arabic syntax. Pro features were investigated practically and theoretically and then, a new mechanism was proposed to derive pro, as well as regular subject, in all Arabic structures. In this mechanism the verb moves to [Spec, T] to check the regular subject features. To indicate the identity of pro in certain structures, the verb moves another time to [Spec, AGR].